PENGARUH MODEL PEMBELAJARAN TIME TOKEN TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAANSKI KELAS VII DI MTSN 1 BENGKALIS - Syah, Mhd. Rizky Chairul (Jurnal Ilmiah Pendidikan dan Keislaman, 2024)
This research is motivated by the problem of low student learning outcomes, lack of active speaking of students in the classroom, due to less effective learning models so that the learning atmosphere often makes students bored, students feel bored quickly, which has an impact on student learning outcomes. Based on this, researchers are trying to use the time token learning model in learning activities to create an active, interesting and fun learning atmosphere. This type of research is quantitative research, then tests and documentation are used to collect research data. The population of this study was all class VII consisting of 224 students with a sample of 2 classes totaling 62 students. In this research, researchers collected data using observation, tests and documentation. The results of the research show that the influence of time token learning on student learning outcomes in class VII SKI subjects at MTsN 1 Bengkalis. Based on testing in SPSS, variable x data shows that the use of the time token learning model can influence student learning outcomes by looking at the score obtained between the experimental class and the control class. From the scores obtained in the experimental class, the control class can be seen that there is a difference in scores, meaning that the experimental class, which uses the time token learning model, gets a higher score than the lecture method. So it can be concluded that using the time token learning model is more effective than using the lecture method. It can be seen from the results of the significant hypothesis test (2 tailed) that the value is 0.000 < 0.05 (smaller than 0.05), so the hypothesis is accepted (ha), there is a difference between the pretest and posttest values. This means that the use of the time token learning model can improve student learning outcomes in the Class VII Ski subject at MTsN 1 Bengkalis